Existence of the Superior Village Chicken Breeders Community Group (Master Pitung) Kendal Regency - Firna Setiawan, David; Eka Prastya Nugraha, Aryan; Galang Windi, Toebagus (KnE Social Sciences, 2024)
Shared interests (hobbies) are one of the factors that encourage the formation of certain communities. Some communities formed from shared interests even have strategic economic potential. One of them is the association of free-range chicken breeders in Kendal district, Central Java province. Currently, the community has a clear goal. However, awareness of the group’s legality does not appear to have been formed. This service program aims to socialize the importance of group legality. The method of service carried out is through group discussion forums. The result of the service program is an increase in the awareness of each member to form a group legally in accordance with applicable legal provisions. The result of the service program is an increase in the awareness of each group member to legalize the association under the name “Master Pitung” or the community of superior village chicken breeders. Keywords: joint business group, superior village chicken breeders